Electroactive polymer (EAP) actuators as artificial muscles : reality, potential, and challenges - Bar-Cohen, Yoseph (SPIE monograph, 2004)
In concept and execution, this book covers the field of EAP with careful attention to all its key aspects and full infrastructure, including the available materials, analytical models, processing techniques, and characterization methods. In this second edition the reader is brought current on promising advances in EAP that have occurred in electric EAP, electroactive polymer gels, ionomeric polymer-metal composites, carbon nanotube actuators, and more.